2011
DOI: 10.1007/s13351-011-0508-7
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of internally and externally mixed anthropogenic sulfate and carbonaceous aerosols on East Asian climate

Abstract: A coupled regional climate and aerosol-chemistry model, RIEMS 2.0 (Regional Integrated Environmental Model System for Asia), in which anthropogenic sulfate, black carbon, and organic carbon were assumed to be externally mixed (EM), internally mixed (IM) or partially internally mixed (IEM), was used to simulate the impacts of these anthropogenic aerosols on East Asian climate for the entire year of 2006. The distributions of aerosol mass concentration, radiative forcing and hence the surface air temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 83 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…e distributions of BC aerosol ground surface concentrations in this study are similar to the results of previous studies, but the concentrations in this study are smaller, which could be caused by the size-resolved scheme [24,25]. Because many previous studies adopted a particle size distribution scheme with a constant scale and simply assumed the radius of BC aerosols to be approximately 0.1 μm [26][27][28]. ey did not accurately consider the presence of BC aerosols with larger particle sizes, which caused the simulated BC aerosol concentrations to be higher than they actually are.…”
Section: Concentration Distribution Of Bc Aerosolssupporting
confidence: 78%
“…e distributions of BC aerosol ground surface concentrations in this study are similar to the results of previous studies, but the concentrations in this study are smaller, which could be caused by the size-resolved scheme [24,25]. Because many previous studies adopted a particle size distribution scheme with a constant scale and simply assumed the radius of BC aerosols to be approximately 0.1 μm [26][27][28]. ey did not accurately consider the presence of BC aerosols with larger particle sizes, which caused the simulated BC aerosol concentrations to be higher than they actually are.…”
Section: Concentration Distribution Of Bc Aerosolssupporting
confidence: 78%
“…This supports the initial hypothesis that a combination of external and core-shell internal mixtures should yield a more realistic representation of the real-world aerosol absorption in the atmosphere. Using a static factor Fin, Zhang et al (2011) and Zhuang et al (2013) also suggested that the partial internal mixing approach has the potential for a more realistic representation of aerosol radiative effects.…”
Section: Resultsmentioning
confidence: 99%
“…Measured concentrations are averaged over corresponding model grids for 1997-2003 and 1995-2004 for the USAQS (PM 2.5 ) and EMEP (sulfate) datasets, respectively. Asian sulfate observations are collected from Liu et al (2009a) and Zhang et al (2011). Figure 2 shows a consistent underestimate of total PM 2.5 over the United States.…”
Section: Model Evaluationmentioning
confidence: 85%